2021
DOI: 10.1093/braincomms/fcab102
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the electrophysiological abnormalities in visually reviewed normal EEGs of drug-resistant focal epilepsy patients

Abstract: Routine scalp EEG is essential in the clinical diagnosis and management of epilepsy. However, a normal scalp EEG (based on expert visual review) recorded from a patient with epilepsy can cause delays in diagnosis and clinical care delivery. Here we investigated whether normal EEGs might contain subtle electrophysiological clues of epilepsy. Specifically, we investigated a) whether there are indicators of abnormal brain electrophysiology in normal EEGs of epilepsy patients and b) whether such abnormalities are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
(53 reference statements)
2
19
0
Order By: Relevance
“…Multiple studies have reported that quantitative analysis of EEG segments without interictal epileptiform abnormalities can reveal subtle nonspecific abnormalities in the normal brain function of patients with epilepsy. [26][27][28][29][30][31][32][33][34] These electrophysiological changes are hypothesized to arise from epilepsy-related pathologic changes such as neuronal loss, gliosis, and synaptic and network changes. They may also reflect interictal dysfunction in memory and cognition because the same neuronal-glial circuits underlying seizure generation in TLE may subserve normal brain functions.…”
Section: Key Pointsmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple studies have reported that quantitative analysis of EEG segments without interictal epileptiform abnormalities can reveal subtle nonspecific abnormalities in the normal brain function of patients with epilepsy. [26][27][28][29][30][31][32][33][34] These electrophysiological changes are hypothesized to arise from epilepsy-related pathologic changes such as neuronal loss, gliosis, and synaptic and network changes. They may also reflect interictal dysfunction in memory and cognition because the same neuronal-glial circuits underlying seizure generation in TLE may subserve normal brain functions.…”
Section: Key Pointsmentioning
confidence: 99%
“…They may also reflect interictal dysfunction in memory and cognition because the same neuronal-glial circuits underlying seizure generation in TLE may subserve normal brain functions. 35,36 The EEG biomarkers of normal brain function investigated in previous studies include alpha activity during eyes-closed wakefulness, [26][27][28][29] spectral connectivity measures based on phase-locking factor [30][31][32] and weighted partial directed coherence, 33 and EEG-based local and global synchrony measures. 34 Furthermore, several of those studies showed that the changes in EEG biomarkers of normal brain function can help determine, a) drug resistance, 26,27,29 b) focal vs generalized origin of seizures, 30,32 and c) seizuregenerating hemisphere in focal epilepsy.…”
Section: Key Pointsmentioning
confidence: 99%
See 3 more Smart Citations